2020
DOI: 10.3390/cryst10090836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Content on the Formation of Inclusions in Fe-5Mn-3Al Steels

Abstract: The effect of N content on the characteristics and formation of inclusions in the Fe-5Mn-3Al steels was investigated in this study. Two synthetic steel melts were produced by two different methods—N2 gas purging and injecting—to introduce nitrogen into the melt. The N content of steel melt varied from 2 to 54 ppm. An increase in the N content to 47 ppm (for 533N-P) and 58 ppm (for 533N-I) increased the total amount of inclusions from 13 to 64 mm−2 and from 21 to 101 mm−2, respectively. The observed inclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is well known that dispersive and fine second‐phase particles refine the grains in steel. [ 11,14–25 ] As previously mentioned, the number of inclusions smaller than 2 μm in the HN steel was significantly greater than that in the LN steel, and AlN inclusions were formed during the smelting process for the HN steel. The fine AlN inclusions acted as the cores of the heterogeneous nucleation of austenite during the solidification process.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…It is well known that dispersive and fine second‐phase particles refine the grains in steel. [ 11,14–25 ] As previously mentioned, the number of inclusions smaller than 2 μm in the HN steel was significantly greater than that in the LN steel, and AlN inclusions were formed during the smelting process for the HN steel. The fine AlN inclusions acted as the cores of the heterogeneous nucleation of austenite during the solidification process.…”
Section: Discussionmentioning
confidence: 78%
“…In general, AlN inclusions are generated during the solidification process with lower Al and N contents and can be formed in molten steel with higher Al and N contents. Alba et al [ 20 ] concluded that the main inclusion was AlN–MnS inclusion in Fe–5Mn–3Al steel, whereas the nitrogen content was less than 10 ppm. With an increase in N content, AlN became the dominant inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas a small portion of MnS is located between Al 2 O 3 and AlN phases in AlON-MnS inclusions (Figure 1c). Detailed inclusion analyses of the current experiments are presented and discussed elsewhere [19,20]. Figure 2 presents the number per unit area (N A ) of complex MnS inclusions observed in the air cooled samples of all experimental steels.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitation and growth of inclusions are closely related to the composition of liquid steel, microsegregation of elements, and cooling rate during solidification. [ 4,6,9–15 ] It is well known that AlN inclusions precipitate during solidification of regular Al‐killed steels containing 0.04–0.05 mass% aluminum. [ 9,16 ] Many researchers [ 9,17 ] have found that AlN could precipitate before solidification of high‐aluminum and high‐nitrogen steel.…”
Section: Introductionmentioning
confidence: 99%